Exchange intervention effect in Colombia : 2004-2006 (2008)
ABSTRACT: This article measures the effectiveness of the exchange interventions executed exerted by the Colombian Central Bank between 2004-2006 from a relative measure for the size of such interventions and its effects on the mean and variance of the nominal exchange rate in the country in such period. The obtained results by means of a relative index of intervention, a GARCH estimation and an impulse-response function, indicate that such interventions had little and transitory effects in the level and variance of the exchange rate, presenting several day delays and being rapidly discounted by the market. Likewise, it is shown that such interventions, executed in a moment when a strong appreciation process of the Colombian peso happened, did not generate inflationary pressures and could moderate, but not revert, the peso/dollar revaluation tendency .